Regional innovation systems in Portugal: A critical evaluation - Santos, Domingos (2018)
Innovation has moved to the foreground in regional policy in the three last decades. Public policies have been shaped by «best practice models» derived from high-tech urban-metropolitan areas and successful regions. However, lessons learned from these examples are rarely transferable elsewhere. The regional innovation systems in peripheral regions, and the likelihood of their acting as instruments for territorial competitiveness, have rarely been the subjects of discussion. The main objective of the article is precisely to take Portugal as an example to enrich this analysis. The first part of this article examines the concept of regional innovation systems against the background of modern theories of innovation and regional policies. It is argued that the role of localized learning is of strategic importance in the promotion of endogenous regional development. The authors then discuss the structural barriers and opportunities to promote regional innovation strategies in the Portuguese political, economic and social context, and, finally, they point out some specificities that need to be addressed in the redesign of public interventions in order to improve regional competitiveness and sustainability.